Synergistic effect of cisplatin chemotherapy combined with fractionated radiotherapy regimen in HPV-positive and HPV-negative experimental pharyngeal squamous cell carcinoma - Simona Kranjc Brezar (Nature Portfolio, 2020)
Abstract HPV infection renders oropharyngeal squamous cell carcinomas more radiosensitive, which results in a favorable prognosis for HPV-positive patients treated with radiation alone or with concurrent platinum-based chemotherapy. The degree of radiosensitivity in fractionated regimens has not yet been fully explored; therefore, in this study, the radiosensitivity of HPV-negative tumors (FaDu) was compared to that of HPV-positive tumors (2A3) subjected to concurrent cisplatin chemotherapy and fractionated versus isoeffective single-dose tumor irradiation in immunodeficient mice. HPV-positive tumors were approximately 5 times more radiosensitive than HPV-negative tumors, irrespective of the irradiation regimen. In both tumor models, concurrent cisplatin chemotherapy and the fractionated regimen induced significant tumor radiosensitization, with a 3- to 4-fold increase in the tumor growth delay compared to that of single-dose irradiation. Furthermore, the degree of radiosensitization induced by cisplatin chemotherapy concurrent with the fractionated irradiation regimen was much higher in HPV-positive tumors, where a synergistic antitumor effect was observed. Specifically, after combined therapy, a 26% higher survival rate was observed in mice with HPV-positive tumors than in mice with HPV-negative tumors. These data suggest that HPV-positive tumors are more radiosensitive to fractionated regimen than to single-dose irradiation with concurrent cisplatin chemotherapy acting synergistically to irradiation.